2021
DOI: 10.1002/jbt.22855
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin B6on brain damage in valproic acid induced toxicity

Abstract: Valproic acid (VPA) is an efficient antiepileptic drug widely used for the treatment of epilepsy and other seizures in both children and adults. It is also reported to have side and toxic effects on many organs and tissues. Vitamin B 6 (Vit B 6 ) is a welldescribed water-soluble vitamin, which has an antioxidant effect. In this study, we aimed to investigate the protective effect of Vit B 6 on VPA-induced brain injury.Male Sprague-Dawley rats were divided into four groups. Group I, control animals;Group II, Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Higher levels of SA in tissues are often associated with increased ROS levels [43,44] . Previous research has shown that valproate administration increases SA levels in the brain tissue of rats [27] . In this study, the administration of moringa extract significantly reduced the SA levels that had been elevated by VA.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…Higher levels of SA in tissues are often associated with increased ROS levels [43,44] . Previous research has shown that valproate administration increases SA levels in the brain tissue of rats [27] . In this study, the administration of moringa extract significantly reduced the SA levels that had been elevated by VA.…”
Section: Resultssupporting
confidence: 50%
“…[43,44] Previous research has shown that valproate administration increases SA levels in the brain tissue of rats. [27] In this study, the administration of moringa extract significantly reduced the SA levels that had been elevated by VA. This reduction is likely due to the antioxidant properties of the compounds in moringa, which helped scavenge ROS species and mitigate the increase in SA levels induced by VA.…”
Section: Resultsmentioning
confidence: 49%
See 1 more Smart Citation
“…Turkyılmaz et al observed that vitamin B 6 has a protective effect on valproic acid-induced brain damage. 36 Vitamin C is used for the prevention and treatment of the common cold, mental illnesses, infertility, cancers, and AIDS. It is a cofactor that has an important role in many biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to that, Raukas et al [ 58 ] reported that they found elevated mitochondrial OSI in brain tissues of Alzheimer's disease patients. Vit U, whose antioxidant activity has been proven on many toxicity models, [ 59,60 ] showed reversing effect on the distorted activities of antioxidants and oxidant levels of the brain tissues of the PTZ administered group.…”
Section: Discussionmentioning
confidence: 99%